Adsorption and Desorption Mechanism of Oil Palm Empty Fruit Bunch Grafted Polyvinyl Alcohol (OPEFB-g-PVA) Hydrogel in Nickel(II) Removal - Rafeek, Mohamed Rizwan (Universiti Teknologi PETRONAS, 2016)
Oil palm empty fruit bunch (OPEFB) fiber is a highly potential natural polymer to be used as efficient and low cost adsorbents of heavy metal cations from waste water. Oil palm empty fruit bunch grafted polyvinyl alcohol (OPEFB-g-PVA) was prepared as Nickel(II) adsorbent. The ultimate objective of this research is to synthesize OPEFBg-PVA and study the adsorption and desorption of OPEFB-g-PVA hydrogel at different weight percent of OPEFB. OPEFB-g-PVA was synthesized by using ammonium persulfate (APS) as initiator and boric acid as the crosslinking agent via solution polymerization. All of the samples were characterized by Fourier Transform Infrared spectroscopy (FTIR), Atomic Absorption Spectroscopy (AAS) and Scanning Electron Microscope (SEM). The wat Besides that, the adsorption and desorption mechanism of the hydrogel was determined by using Langmuir isotherms.